Research on the Structure Design of Composite Water-lubricated Stern Bearing - Yanzhen Wang; Tao Zhong; Xiuli Zhang; Zhongwei Yin (Jixie chuandong)
Based on the ANSYS CFX fluid-structure interaction numerical calculation method， the lubrication performance and structure design of water-lubricated composite stern bearing are studied， the effects laws of different grooves， clearance ratios， length diameter ratio， and diameters on load carrying capacity， water film pressure， bearing deformation， minimum water film thickness and bearing friction coefficient are expounded. In addition， by using a water-lubricated bearing test rig， the effects of different water grooves on the starting friction torque， transition speed， and friction coefficient of the bearing are studied. The results show that the friction coefficient， maximum water film pressure， and maximum bearing deformation increase with the number of water grooves. The load carrying capacity and minimum water film thickness decrease with the increase of clearance ratio while increase with the increase of length diameter ratio. Finally， the variation of load carrying capacity with a diameter of 100~500 mm， length diameter ratio of 2~3， and clearance ratio of 0.1%~0.2% is summarized. A certain theoretical basis for the design of water-lubricated stern bearings is provided.